Association between breastfeeding duration and BMI, 2009–2018: a population-based study - Sun, Jiaqing; Han, Jian; Jiang, Xiaofeng; Ying, Yali; Li, Shenghao (Frontiers in Nutrition, 2024)
Background In the 21st century, childhood overweight and obesity have become major public health issues worldwide. Previous studies have shown that breastfeeding helps prevent overweight or obesity in children. Despite the significant advantages of breastfeeding, the global exclusive breastfeeding rate for infants under 6 months old is only 40%, while in the United States, the rate is only 25%. The aim of this study is to explore the relationship between breastfeeding duration and BMI in children aged 2 to 6 in the United States, and to raise awareness of breastfeeding. Methods A cross-sectional study included 2,769 participants between the ages of 2 and 6 from a sample that represented the entire NHANES 2009–2018. Data was analyzed using EmpowerStats, (www.empowerstats.com) linear regression as well as Chi-square test, t-tests, multivariate regression analysis and smooth cure fitting were done. Results Breastfeeding duration long-term group exhibited a statistically significant negative association with BMI, with a regression coefficient of −0.21 (P < 0.05). The continuous analysis of breastfeeding duration by tertile also demonstrate a statistically significant negative association with BMI. Subgroup analysis revealed that the potential benefits of breastfeeding on BMI were more obvious in low-income environments and maternal age 18 to 35 years, with a regression coefficient of −0.57 and −0.24, respectively (all P < 0.05). Conclusion The findings emphasize the importance of breastfeeding in reducing childhood overweight/obesity and preventing associated diseases, both in clinical and public health settings.